Near-Infrared Intraoperative Imaging Can Successfully Identify Malignant Pleural Mesothelioma After Neoadjuvant Chemotherapy - Jarrod D. Predina MD, MTR; Andrew Newton MD; Greg Kennedy BA; M. Kenneth Lee MD, PhD; Sunil Singhal MD (Molecular Imaging)
Malignant pleural mesothelioma is a deadly disease. Complete surgical resection provides patients with the best opportunity for long-term survival. Unfortunately, identification of disease during resection can be challenging. In this report, we describe successful intraoperative utilization of the near-infrared imaging agent, indocyanine green, to help the surgeon identify malignant disease in a patient with malignant pleural mesothelioma who had previously received neoadjuvant chemotherapy. This technology may ultimately enhance the thoracic surgeon’s ability to identify small disease deposits at the time of resection.